IMPACT OF REARING SPACE, LEAF QUALITY, DIET RATIONING AND SANITATION MEASURES ON BIVOLTINE SILKWORM REARING IN THE PLAINS OF WEST BENGAL INDIA - DAS, S.; GHOSH, M.K.; SHAMSUDDIN, M.; SAHA, P.K.; SEN, S.K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1993)
To improve the rearing performance of bivoltine silkworms combined effects of rearing space, leaf quality, diet rationing and sanitation has been studied. It is observed that except hot summer the combination of wider Chinese spacing, tender leaf feeding, 20% rationing from optimum diet and two times bed cleaning daily (T) gave significantly better rearing results over Indian spacing, mature leaf feeding, no diet rationing and once bed cleaning (T2). The reverse is true in hot summer. The probable reasons for such difference have been discussed.